EFEKTIVITAS KINERJA SATUAN POLISI PAMONG PRAJA DALAM MENERTIBKAN PEDAGANG KAKI LIMA DI KABUPATEN SABU RAIJUA - Cornyella Messak, Imanuella Wilhelmine; Lay, Marthina Raga; Seran, Delila A. Nahak; Benyamin, Rouwland Alberto (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This research aims to describe the effectiveness of the performance of the civil service police unit in controlling street vendors in Sabu Raijua Regency. The method used in this research is qualitative with data collection techniques used, namely: interviews, documentation and observation. The theory used is the Performance Effectiveness theory from Agus Dwiyanto (2021). The results of this research indicate that the effectiveness of the performance of the civil service police unit in controlling street vendors in Sabu Raijua district has not been optimal in terms of indicators: 1) The productivity of public services by the civil service police unit has not been good enough. There are still complaints from traders regarding the control which affects their income and complain about economic losses due to the lack of market visitors, 2) Quality of Service in this case, the provision of facilities and infrastructure is still less than optimal due to unstable electricity in the Nataga market, resulting in traders' fish being damaged and not selling, 3) Responsiveness in controlling street vendors has been carried out through socialization and an agreement not to sell in Seba shops, however, there are still many sellers who return to selling after duty hours are over, 4) Responsibility implementation of responsibility in controlling street vendors still faces challenges such as the absence of specific regional regulations in regulating street vendors so that it is difficult to enforce order, 5) Accountability, Satpol PP's efforts in controlling street vendors in Sabu Raijua district show that there is a good application of accountability, namely by prioritizing polite communication and avoiding violence and Satpol PP is also trying to build harmonious relationships with street vendors and the local community.